(untitled) (Journal Of Educational and Psychological Researches, 2024)
The study aims to identify the extent to which the students of the fourth stage, Department of Geography, possess pivotal thinking skills. To achieve the objective of the research, the researchers adopted the descriptive research method. To measure pivotal thinking skills, the researcher developed a scale consisting of 40 items with three alternatives (always, sometimes, and never) administered to a sample of 50 students. The result of the t-test for one sample showed that there are statistically significant differences at the level of significance (0.05) between the real averages of 102.18% degrees, which is greater than the hypothetical mean of 60 degrees. This indicates that the students in the research sample possess pivotal thinking skills. Students need programs aimed at developing thinking skills. The recommendations indicated the need to focus on raising the motivation of female students to develop their scientific curiosity and directing the equipment unit in the Directorate of Education to supply school laboratories with everything new whenever possible.